Bibliometric analysis of enegep publications on education in Production Engineering between 2016 and 2020 (Research, Society and Development, 2021)
Research on teaching in certain professional areas is important to understand the learning dynamics, thus revealing the importance of Education in Production Engineering and its impact on higher education courses. Furthermore, although this theme is not as representative in the area, it is of great value for the training of Production Engineers. Thus, this study aimed to analyze the themes and methodologies presented in the articles submitted to the National Meeting of Production Engineering - ENEGEP. To meet the objectives, a bibliographic and bibliometric review was carried out from the annals of the event for the years 2016 to 2020, considering the area of ​​Education in Production Engineering and its sub-areas. The searches resulted in 214 works, among which the Study of Production Engineering Teaching and Study of the Development and Application of Research in Production Engineering were identified as the main areas. As for the research methods used, the Theoretical/Conceptual prevailed. Thus, 214 works were obtained and analyzed to identify the main areas addressed in the period: Study of Production Engineering Education and Study of the Development and Application of Research in Production Engineering.